2014
DOI: 10.3390/nu6062229
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Fortification Decreases ZIP1 Gene Expression of Some Adolescent Females with Appropriate Plasma Zinc Levels

Abstract: Zinc homeostasis is achieved after intake variation by changes in the expression levels of zinc transporters. The aim of this study was to evaluate dietary intake (by 24-h recall), absorption, plasma zinc (by absorption spectrophotometry) and the expression levels (by quantitative PCR), of the transporters ZIP1 (zinc importer) and ZnT1 (zinc exporter) in peripheral white blood cells from 24 adolescent girls before and after drinking zinc-fortified milk for 27 day. Zinc intake increased (p < 0.001) from 10.5 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Moving forward, future research should further characterize the use of metallothionein as a biomarker of zinc status, such as whether metallothionein can be used in adolescents and children or individuals with disease. Although the authors did not determine metallothionein expression, one study not included in this systematic review examined ZnT1 and ZIP1 expression in leukocytes isolated from 12-to 16-y-old female patients (41). In agreement with Andree et al (24), the authors reported a decrease in ZIP1 with zinc supplementation; however, no change was observed in ZnT1 or plasma zinc concentrations.…”
Section: Discussionsupporting
confidence: 51%
“…Moving forward, future research should further characterize the use of metallothionein as a biomarker of zinc status, such as whether metallothionein can be used in adolescents and children or individuals with disease. Although the authors did not determine metallothionein expression, one study not included in this systematic review examined ZnT1 and ZIP1 expression in leukocytes isolated from 12-to 16-y-old female patients (41). In agreement with Andree et al (24), the authors reported a decrease in ZIP1 with zinc supplementation; however, no change was observed in ZnT1 or plasma zinc concentrations.…”
Section: Discussionsupporting
confidence: 51%
“…Zip1 is the major zinc apical transporter in the small intestine, 76 and it has been shown that increasing dietary zinc consumption leads to an increase of the expression of Zip1 in the small intestine. 79 ZnT1 has been observed to increase with rising zinc levels, this might be to avoid excessive accumulation of zinc in the cytosol by removing Zinc through the basolateral chamber of the small intestine. 80,81 We observed that ZnT1 was significantly upregulated for the medium and high doses in DMEM (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this hypothesis, Zn supplementation led to a diminution of SCL39A1 transcriptional expression in primary cultures of adult rat ventricular myocytes [348]. Comparable results have been obtained in humans, with some female adolescent showing an increase in SLC39A1 mRNA expression in blood leucocytes following Zn supplementation with Zn-fortified milk for 27 days [349]. While an increase in SLC39A1 mRNA levels were not observed in all individuals from the treated group [349], comparable results have been obtained in humans by another group, demonstrating an increased ZIP1 mRNA expression in lymphocytes in an Australian elderly population supplemented with Zn [350].…”
Section: Zip1 (Slc39a1)supporting
confidence: 55%
“…Comparable results have been obtained in humans, with some female adolescent showing an increase in SLC39A1 mRNA expression in blood leucocytes following Zn supplementation with Zn-fortified milk for 27 days [349]. While an increase in SLC39A1 mRNA levels were not observed in all individuals from the treated group [349], comparable results have been obtained in humans by another group, demonstrating an increased ZIP1 mRNA expression in lymphocytes in an Australian elderly population supplemented with Zn [350]. Lastly, ZIP1 is associated with various cancers [351][352][353], including pancreatic [287] and prostate [354][355][356][357] cancer.…”
Section: Zip1 (Slc39a1)mentioning
confidence: 76%